Design and Development of Auto Depth Control of Remotely Operated Vehicle (ROV) using Thruster System - Ali, Fara Ashikin; Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Sulaima, Mohamad Fani; Ismail, Jaaffar (2013)
Remotely Operated Vehicle (ROV) is one of the underwater robot that designed on purpose for surveillance, monitoring and collecting data for underwater activities. In underwater vehicle industries, thruster is an important part in controlling the direction, depth and speed of the ROV. However, there are some of the ROV that cannot maintain at specified depth for a long time because of disturbance and so on. This paper proposed an auto depth control using a thruster system. A prototype of thruster with an auto depth control is developed and attached onto the previous fabricated UTeM ROV. This paper presents the operation of auto depth control as well as submerging and emerging uses thrusters and maintaining at the specified depth. The thruster system utilizes a microcontroller as its brain, piezoresistive strain gauge pressure sensor as a pressure sensor and a DC brushless motor to run the propeller. The performance analysis of the auto depth control system is performed to identify the sensitivity of pressure sensor, the accuracy and the stability of the system. The results show that the thruster system gives a good performance in maintaining at specified depth as well as stabilized itself when a disturbance occurred.